The concept of a communication event – in the polish legal system - Migdał, Dawid; Wieczorek, Oliwia (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
In order to create a basis for further considerations, it is necessary to explain the basic concept of a communication event. There is no such definition in the doctrine; it must be sought in other sources. An example of such a place is, of course, the PWN Polish language dictionary (PWN, 2021) , according to which an event is "something that happened". Communication, in turn, is the movement of means of transport between distant places, e.g. roads (PWN, 2021) . By combining these two definitions, it can be stated that a traffic event is a situation that occurred on the road in which at least one vehicle was involved - it does not have to be a motorized vehicle, and the effect of such an event is destruction of property, damage to health, and sometimes even the death of the person involved in the incident (ZPE, 2022) . Of course, for such an event to occur, there must be additional factors apart from the road itself, such as a person and a vehicle.